Effect of initial wetting state on plastron recovery through heating. (August 2020) - Barghi, F.; Entezari, M.; Chini, S.F.; Amirfazli, A.
Highlights: Applicability of superhydrophobic surfaces depends on maintaining the trapped gas pockets. It is desirable to restore the lost plastron underwater by heating. Initial wetting state affects the possibility of plastron recovery. The boiling for Cassie–Baxter state skips nucleate regime and leads to film boiling. The boiling for Wenzel state remains in nucleate regime. The boiling for parahydrophobic state starts with nucleate and switches to film boiling regime. Abstract: Applicability of superhydrophobic surfaces depends on maintaining the trapped gas pockets in the micro/nano roughness valleys of the surface. It is well known that besides efforts of scientists to construct robust surfaces against wetting transition, it is also desirable to develop strategies to restore the lost plastron underwater. The current paper systematically investigates the effect of initial wetting state on the possibility of plastron recovery. It is shown that different temperature for water and surface as well as different air solubility in water can result in different wetting state. It is also shown that despite the Cassie–Baxter state which skips nucleate boiling and leads to film boiling, in Wenzel state, heating results in nucleate boiling and nucleate bubbles easily detach from the surface due to strong contact line pinning. Interestingly, when surface has parahydrophobic behavior (water wets the micro structures but the nano features remain dry), the plastron is revivable through existing air in the water; but if we degas the water the plastron can be recovered by applying heat flux.